2008
DOI: 10.1007/s12288-008-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Hematological malignancies diagnosed by bone marrow examination in a tertiary hospital at Uttarakhand, India

Abstract: Introduction Hematological malignancies are quite common and affect all ages and genders. The diagnosis involves a multiparameter approach. The geographical distribution of various types of hematological malignancies has been provided by various authors but no such data have been published regarding the State of Uttarakhand in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
2
9
2
Order By: Relevance
“…Bleeding was also a common presenting feature. Similar findings have been reported in other studies on AML [11,12]. Rogers et al have documented that pallor and fever were prominent feature in majority of subtypes [14].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Bleeding was also a common presenting feature. Similar findings have been reported in other studies on AML [11,12]. Rogers et al have documented that pallor and fever were prominent feature in majority of subtypes [14].…”
Section: Resultssupporting
confidence: 90%
“…A lot of preceding studies had stated a greater incidence of AML in males though the male prevalence is not as distinctive as in ALL [5,6] in a study by male preponderance was also present, with a male to female ratio of 1.61:1.0. Greater incidence of all leukemia in males appears to rise as males are relatively more exposed to work-related and environmental hazards as has been submitted by some studies [10][11][12]. As regards age it was observed that at the time of presentation majority of patients (85.9%) was in the group of 25-60 years and only 14.1% of cases were in between 10-25 years of age.…”
Section: Resultsmentioning
confidence: 80%
“…Compared with the data from other studies carried out in a single center, the frequency of our HM (20.7 NC/year) is similar to that found by Koulidiati, in Burkina Faso and Thiam, in Senegal which were respectively 22.13 and 22.14 NC/year. 5,16 This result is also consistent with the overall incidence of HM found in African studies, which was 5.28 NC/year for Mahboub et al, 16 4,5,7,[16][17][18][19][20][21] The frequency of our HM is nevertheless lower than that found in the Asian monocentric studies for which the frequency of HM which was 27.1 NC/year for Kusum et al, 30 NC/year for Idris et al, 69.7 NC/year for Al-ghazali et al, and 75 NC/year for Al-Kahiri et al 6,13,22,23 The frequency of our HM is far lower than that found in multicenter studies such as those of Errahhali et al, in Morocco and Hossain et al, in Bangladesh for which it was respectively 132 and 1002.6 NC/year. 12,24 The frequency of our HM is also far lower than that found in the cancer registries of countries possessing these tools: HM frequency was 363.2 NC/year for Broccia et al, in Sardinia (Italy), 2,700 NC/year for McNally et al, in United Kingdom and 230,000 NC/year for Rodriguez-Abreu in Europe.…”
Section: Discussioncontrasting
confidence: 66%
“…Lymphoid neoplasm included MBCN 43.6%, ALL 7.3%, HL 5.5% and MTCN 3.6%. In this study, Plasma cell Neoplasm (PCN) (29%) was the commonest lymphoid neoplasm followed respectively by Non Hodgkin Lymphoma (NHL) 14 We had two Patients less than 20 years of age, T ALL and LCH was seen accounting each o.9% of HM. In young adult Patient of 21 to 40 years of age, NHL was the most common HM with 9.09% followed by AML 4.5%, MPN (CML) 4.5%, B ALL 2.7%, T ALL 0.9%, HL 0.9% and LCH 0.9%.…”
Section: Resultsmentioning
confidence: 99%
“…CLL, AML, ALL, and finally MDS. 7 PCN (Multiple myeloma) has been seen to affect males for frequently 14. In female also, Lymphoid Neoplasm was most frequent HM with 14.5% followed by Myeloid Neoplasm of 11.8%.…”
mentioning
confidence: 99%